SHAREHOLDER AGREEMENTS IN PRIVATE COMPANIES: A TOOL FOR GOVERNANCE OR A SOURCE OF CONFLICT? (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This dissertation investigates the dual role of shareholder agreements in private companies, examining them as both governance tools and potential sources of conflict. The research centers on elucidating how the terms and enforcement of these agreements influence shareholder relations and the overall performance of companies. Employing qualitative methods, including interviews with company executives and in-depth analysis of case studies involving disputes linked to shareholder agreements, the study reveals that while well-structured agreements can enhance governance by clarifying expectations and minimizing disputes, poorly constructed or ambiguously phrased agreements often lead to significant conflicts. These conflicts are found to adversely affect company performance, especially in high-stakes environments such as the healthcare sector, where effective governance is crucial for operational success and sustainability. The findings underscore the critical importance of carefully drafting and enforcing shareholder agreements to foster collaboration and align interests among stakeholders. This research contributes to the broader field of healthcare by highlighting how governance mechanisms influence organizational dynamics and stakeholder engagement, ultimately informing best practices for corporate governance within the context of healthcare management. By illuminating the balance between promoting effective governance and mitigating conflict, this dissertation offers valuable insights for practitioners and policymakers striving to enhance governance structures in private companies, thereby facilitating better decision-making processes and improving overall healthcare outcomes.